2013
DOI: 10.1186/1477-5956-11-38
|View full text |Cite
|
Sign up to set email alerts
|

Label-free mass spectrometry proteome quantification of human embryonic kidney cells following 24 hours of sialic acid overproduction

Abstract: BackgroundCell surface glycoprotein sialylation is one of the most ubiquitous glycan modifications found on higher eukaryotes. The surface sialylation pattern of cells is influenced by the cellular environment but also by the Golgi sialyltransferase activity and flux of metabolites through sialic acid producing pathways. Altered cell surface sialic acid patterns have been observed in several cancers and other pathological conditions. In this experiment we examined the cellular proteomic changes that occur in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…Protein expression bands of interest were normalised relative to stain‐free total protein (Parviainen et al . ). Gene data were analysed with a two‐way ANOVA to determine differences between treatment and sex for each placental region (labyrinth and junctional zone), with a Student's t test used to identify where interactions lie.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Protein expression bands of interest were normalised relative to stain‐free total protein (Parviainen et al . ). Gene data were analysed with a two‐way ANOVA to determine differences between treatment and sex for each placental region (labyrinth and junctional zone), with a Student's t test used to identify where interactions lie.…”
Section: Resultsmentioning
confidence: 97%
“…Protein expression bands of interest were normalised relative to stain‐free total protein (Parviainen et al . ) and expressed as values relative to Control males.…”
Section: Methodsmentioning
confidence: 99%
“…As we discussed previously [35], the transit time across the plateau is typically much shorter than the elution time, meaning that the total time described in Equation 10 further simplifies to the first term,…”
Section: Drag Forcementioning
confidence: 99%
“…In the past few decades, several advances coupling drift tube IMS and other time-dispersive methods (i.e., traveling wave IMS) to mass spectrometry (MS) [1][2][3][4][5][6][7][8][9][10] have extended its versatility for a range of chemical [11][12][13][14][15][16][17], physical [18][19][20][21][22][23], and biomolecular structural studies [24][25][26][27][28][29][30][31][32][33]. Still relatively new to the biomedical field, several groups have recently begun to incorporate LC-IMS-MS workflows in proteomics studies [34][35][36][37], and enhanced performance has been demonstrated [38]. Given the recent rate of growth in the IMS field [39] and its broad analytical utility, it seems prudent to expect that full maturity-both in terms of application workflows and technology performance-is yet to come.…”
Section: Introductionmentioning
confidence: 99%
“…A typical proteomics experiment usu ally involves separation and isolation of proteins from a sample, acquisition of their structures and their characterization, is calculated on the basis of the differ ences between the areas of the XICs of the two ions with the same mass (46). The labeling of these ions with isotopes can provide a more accurate result, but the cost involved is much higher than the labelfree method, and complex sam ple processing for this method can lead to sample loss.…”
Section: Proteomics Technologiesmentioning
confidence: 99%